INSAT2010 - Inquérito Saúde e Trabalho: outras questões, novas relações - Carla Barros-Duarte; Liliana Cunha (Universidade do Porto, 2010)
The INSAT, as an instrument that mediates the statements of the work´s impact on heath has already a history that we will try to unveil. For that purpose we will refer to the activity sectors considered in previous analyses conducted with this instrument; to the problems found in some of these contexts and work situations; to the arguments that justify a more precise study of other relationships between the variables considered in the inquiry. Finally, the portrait and the interpretation of INSAT´s history contribute to its acknowledgement as a "living" instrument, now reformulated considering the evolutions of work, as well as the reflections elicited by its use.